Nghiên cứu xác định năng lượng hoạt hóa quá trình catalaza của phức xúc tác [Co(Acac)]+ - Huỳnh, Lê Văn; Quỳnh Chi, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
Catalytic activity of the complex [Co(Acac)]+ is similar to the catalytic activity of the enzyme. Catalytic complex [Co(Acac)]+ acts as a mediator for electron transport between catalyst and substrate complexes and restored after reaction. Under the effect of the catalyst complex, making the chemical reactions happed more easily, in softer conditions than with no catalyst. Every a shift or orientation of the electron is accompanied by a certain loss of energy. A catalyst is considered to be highly effective, as it makes the process occurs with at least an intermediate stage, minimizing energy for the rotation or the new arrangement. This paper is the research results identify activation energy of catalytic complex created by Co2+ with Acetylacetone (Acac) in the process of catalyze is E* = 8.976 kcal/mol, as well as determine the enthalpy is DH*298= 8.384 kcal/mol, entropy is DS* = -39.0 cal/mol, the free energy is DG* = 20.01 kcal/mol and formed constant is K* = 5.75×10-13 l.mol-1.s-1. The research results are a scientific basis for the research and application of complex homogeneous catalytic redox processes in the production technology. Keywords: Activation energy of the catalytic complex, enzyme, catalyst